2017
DOI: 10.1038/srep40361
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/AKT pathway via GLI1 inhibition enhanced the drug sensitivity of acute myeloid leukemia cells

Abstract: Combination targeted therapy is commonly used to treat acute myeloid leukemia (AML) patients, particularly in refractory/relapse (RR) population. However, concerns have been raised regarding the safety and patient tolerance of combination chemotherapy. It is critical to choose the appropriate treatment for precision therapy. We performed genome-wide RNA profiling using RNA-Seq to compare the RR group and the complete remission (CR) group (a total of 42 adult AML patients). The Hedgehog (Hh) and PI3K/AKT pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Gli1 can be regulated by specific serine/threonine kinases (34,(36)(37)(38), and we have demonstrated that DGT inhibits GSK3b activity, which are known to be associated with osteosarcoma progression and poor patient outcome. Therefore, we hypothesized that GSK3b activity is involved in DGT-induced Gli1 repression in osteosarcoma.…”
Section: Dgt Downregulates Gli1 Expression and Activation Mainly By Bmentioning
confidence: 99%
“…Gli1 can be regulated by specific serine/threonine kinases (34,(36)(37)(38), and we have demonstrated that DGT inhibits GSK3b activity, which are known to be associated with osteosarcoma progression and poor patient outcome. Therefore, we hypothesized that GSK3b activity is involved in DGT-induced Gli1 repression in osteosarcoma.…”
Section: Dgt Downregulates Gli1 Expression and Activation Mainly By Bmentioning
confidence: 99%
“…47 Meanwhile, sustained activation of the PI3K/AKT pathway accompanied with deletion of PTEN has been identified in different types of leukemia. 6 Targeting the PI3K/AKT/mTOR pathway may have pro-apoptotic and anti-proliferative effects on hematological malignancies through simultaneous targeting of Bcl-2/Bcl-xL pathways represent an effective anti-leukemic strategy via down-regulation of Mcl-1 and up-regulation/activation of Bak, Bax, Bim, and Bad. 48 Many appearances properties of MSCs that include anti-apoptosis, growth factor production, neuroprotection, anti-fibrosis, and chemo-attraction provide a broad spectrum for its using in disease therapies.…”
Section: Discussionmentioning
confidence: 99%
“…5 Acute amyloid leukemia involving different signaling pathways are expected to be involved in the clinical treatment of acute amyloid leukemia. 6 The PI3K/AKT/mTOR signaling pathways are detectable and activated in most cases of AML. Inhibition of PI3K/AKT or mTORC1 signaling pathways suppresses the proliferation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt pathway is an intracellular pathway that plays a critical role in apoptosis and cancer, whose components are often altered in cancer, leading to dysregulated apoptosis and chemoresistance [78]. Chen et al demonstrated that the PI3K inhibitor LY294002 can directly target LSCs without adverse reactions to normal HSCs, and they found that PI3K and NF-κB may coexist in the same signaling pathway [79].…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%